Effort of EAI Projects: A Repertory Grid Investigation of Influencing Factors. Issue 5 (October 2015) - Wagner, Holger; Pankratz, Oleg; Mellis, Werner; Basten, Dirk
Many companies struggle with effective and efficient accomplishment of enterprise application integration (EAI), resulting in significant time and budget overruns. Concerning project management, a major reason for failure is considered to be effort underestimation. This underestimation is an aftermath of applying estimation methods that do not account for all relevant factors influencing EAI project effort. Applying the Repertory Grid Technique, we explore factors affecting the effort of such projects by conducting 22 semi-structured expert interviews. We provide an extensive overview of 91 effort-influencing factors and their classification in nine categories, which can be used as a checklist in EAI projects.